ATIM-10. A PHASE I/II CLINICAL TRIAL OF AUTOLOGOUS CMV-SPECIFIC CYTOTOXIC T CELLS (CMV-TC) FOR GLIOBLASTOMA: DOSE ESCALATION AND CORRELATIVE RESULTS. (5th November 2018) - Penas-Prado, Marta; Weathers, Shiao-Pei; Zhou, Shouhao; Kamiya-Matsuoka, Carlos; O'Brien, Barbara; Loghin, Monica; Harrison, Rebecca; Pei, Be Lian; Ictech, Sandra; Hunter, Kathy; Yung, W K Alfred; de Groot, John; et al.
Abstract: BACKGROUND: Cytomegalovirus (CMV) antigens are present in > 90% of GBMs but not in normal brain. CMV-TC in GBM tumor tissue have their effector function suppressed. Highly functional CMV pp65 specific T cells can be expanded in vitro from peripheral blood (PB) of GBM patients. METHODS: Autologous polyclonal CD8+ and CD4+ CMV-TC from patients with recurrent GBM were expanded ex vivo under GMP-compliant conditions and administered after 3 weeks of lymphodepleting dose-dense temozolomide (ddTMZ, 100 mg/m2); 4 dose levels (5 x 10 6 cells to 1 x 10 8 cells), 3 + 3 design. Treatment was repeated q 6 weeks; total of 4 cycles. Eligibility: ≥18 years of age, KPS ≥60, CMV sero+, on ≤ 2 mg of dexamethasone daily, any number of relapses. Imaging response evaluated by MRI q 6 weeks. In vivo persistence and expansion of adoptively-infused CMV-TC determined by dextramer staining and multiparameter flow cytometry in serially-sampled PB. RESULTS: 34 patients screened, 18 underwent leukapheresis, 15 completed cycle 1. Median age 56 (27–69), median KPS 90; 11 were at 1st, 3 at 2nd and 1 at 3rd relapse. MGMT methylated in 6, unmethylated in 3, indeterminate/unknown in 6. IDH status wildtype in 10, mutated in 3, unknown in 2. No dose limiting toxicities (DLTs) observed. Complete radiographic response observed in 1 patient, partial response in 2, stable disease in 6, and progressive disease in 6. Repeated infusions of CMV-TC were associated with significant increase in circulating CMV+ CD8+ T-cells, but cytokine production (CD107a, TNFα, IFNγ, IL2) was suppressed (dose level 4 analysis ongoing). CONCLUSIONS: Adoptive infusion of CMV-TC after lymphodepleting therapy with ddTMZ was well tolerated with no DLTs; 1 x 10e8 confirmed as safe dose. Effector function in PB was suppressed. Correlative studies of CMV-specific T cell effector function in tumor microenvironment will be assessed in window-of-opportunity expansion cohort.